The 2010 International Conference on Green Circuits and Systems 2010
DOI: 10.1109/icgcs.2010.5542987
|View full text |Cite
|
Sign up to set email alerts
|

Learning the local molecular pattern of Alzheimer's disease by non-negative matrix factorization

Abstract: Gene microarray technology is an effective tool to monitor simultaneous activity of multiple cellular pathways from thousands of genes in a single chip. Many clustering methods have been developed to identify groups of genes or experimental conditions that exhibit similar expression patterns from gene expression data, such as hierarchical clustering, k-means, and self-organizing maps (SOM). The limitations of these clustering algorithms are: they group genes (or conditions) based on global similarities in thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…One of the most popular applications of NMF in Bioinformatics is the Gene-expression Analysis [ 6 , 7 ]. It is based on the Microarray Technology , which is a powerful method able to monitor the expression level of thousands of genes, or even whole genomes, in a single experiment [ 44 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most popular applications of NMF in Bioinformatics is the Gene-expression Analysis [ 6 , 7 ]. It is based on the Microarray Technology , which is a powerful method able to monitor the expression level of thousands of genes, or even whole genomes, in a single experiment [ 44 ].…”
Section: Methodsmentioning
confidence: 99%
“…NMF decomposes a large input dataset into a small set of highly interpretable and additive parts. This property has centered the attention of scientists for a wide range of applications in Bioinformatics, such as gene-expression analysis [ 6 , 7 ], scientific literature mining [ 8 ], neuroscience [ 9 ], and several -omics techniques [ 10 , 11 ]. A good review of some of them can be found in [ 12 ].…”
Section: Introductionmentioning
confidence: 99%